Proportional reasoning in the artisan personality type: A case study of high school students in trigonometry ratios - Ramlan, Andi Mariani; Budayasa, I Ketut; Rahaju, Endah Budi (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Proportional reasoning is a critical component of mathematical competence that should be developed at the senior high school level, as it fosters both foundational and advanced mathematical understanding. Educators frequently encounter variations in proportional reasoning abilities among students, often influenced by individual personality types. However, limited research has specifically investigated the proportional reasoning capabilities of high school students with artisan personality types. This study aims to examine the strategies and approaches utilized by students with Artisan Personality Types (APT) in solving trigonometric comparison problems. Employing a qualitative descriptive methodology within a case study design, the research focused on high school students identified as having APT. Data were collected using proportional reasoning tasks, the Keirsey Personality Type Questionnaire, and structured interviews. The analysis was conducted qualitatively, with findings categorized based on established indicators of proportional reasoning. Results indicate that APT students demonstrate the ability to address proportional reasoning problems related to covariation, ratios, and proportions, employing distinct strategies and logical reasoning. Nevertheless, instances of both correct and incorrect responses were observed, often stemming from misinterpretations of the problem context. These findings provide valuable insights for future studies aimed at designing targeted instructional strategies and developing learning tools to enhance the proportional reasoning skills of students with APT.